Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) dalam Upaya Meningkatkan Peran Aktif Mahasiswa Pendidikan Matematika pada Mata Kuliah Kalkulus Diferensial - Rohmah, Siti Nur (Universitas Muhammadiyah Surakarta, 2018)
This research aims to improve the students’ active engagement in diferential calculus learning using a cooperative learning model type Student Teams Achievement Division (STAD). The subject of this research was students of mathematics education department of Universitas Ahmad Dahlan who enrolled in the second semester of 2016/2017 academic year. It was classroom action research conducted in two cycles. Each cycle consisted of : planning, action, observation, and reflection activities. The results suggested that there is an improvement of the students’ active engagement, as it was shown by the positive result given by the students towards the interview. The score of active engagement also improved from 54.99% at the first cycle to 71.03% at the second cycle.